Bokashi Sus Scrofa Fertilizer on Sweet Corn Plant Growth - Murnihati Sarumaha; Bestari Laia; Darmawan Harefa; Lies Dian Marsa Ndraha; Indah Permata Sari Lase; Tatema Telaumbanua; Fatolosa Hulu; Baziduhu Laia; Kaminudin Telaumbanua; Amaano Fau; Andrian Novialdi (Haga : Jurnal Pengabdian Kepada Masyarakat, 2022)
This study aims to determine the effect of bokashi fertilizer Sus scrofa manure on growth sweet corn (Zea mays L.). This type of research is a quantitative study with a pure experimental method (true experiment). The population of this study were 30 polybags of sweet corn. The research sample used a sample consisting 30 polybags sweet corn with treatment and five replications. The treatments applied were P0 (without bokashi), P1 (50 grams), P2 (70 grams), P3 (90 grams), P4 (110 grams), and P5 (130 grams). The data of this study were analyzed using the Kolmogorov-Smirnov test for normality test, homogeneity test and Anova test and test with the LSD test using version 20 of the SPSS (system product and service solution) application. Based on the results the study it was concluded that, It is used for the growth sweet corn plants and the bokashi fertilizer Sus scrofa dung is easy to find and can be processed quickly and the use Sus scrofa dung bokashi fertilizer has an effect on the growth in height, diameter and number leaves of sweet corn (Zea mays L.).